Deregulated expression of a longevity gene, Klotho, in the C9orf72 deletion mice with impaired synaptic plasticity and adult hippocampal neurogenesis - Ho, Wan Yun (2021)
Hexanucleotide repeat expansion of C9ORF72 is the most common genetic cause of amyotrophic lateral sclerosis and frontotemporal dementia. Synergies between loss of C9ORF72 functions and gain of toxicities from the repeat expansions contribute to C9ORF72-mediated pathogenesis. However, how loss of C9orf72 impacts neuronal and synaptic functions remains undetermined. Here, we showed that long-term potentiation at the dentate granule cells and long-term depression at the Schaffer collateral/commissural synapses at the area CA1 were reduced in the hippocampus of C9orf72 knockout mice. Using unbiased transcriptomic analysis, we identified that Klotho, a longevity gene, was selectively dysregulated in an age-dependent manner. Specifically, Klotho protein expression in the hippocampus of C9orf72 knockout mice was incorrectly enriched in the dendritic regions of CA1 with concomitant reduction in granule cell layer of dentate gyrus at 3-month of age followed by an accelerating decline during aging. Furthermore, adult hippocampal neurogenesis was reduced in C9orf72 knockout mice. Taken together, our data suggest that C9ORF72 is required for synaptic plasticity and adult neurogenesis in the hippocampus and Klotho deregulations may be part of C9ORF72-mediated toxicity.